Development, implementation, and evaluation of Sit Less at Work interventions in diverse organisations: a mixed-methods study. (November 2021) - Mackenzie, Kelly; Such, Elizabeth; Norman, Paul; Goyder, Elizabeth
Abstract: Background: Increasingly, workplace health initiatives have targeted workplace sitting with mixed results, suggesting that effectiveness depends on context. This study aimed to explore contextual factors that influence the development, implementation, and evaluation of Sit Less at Work interventions, and to test and refine an operational framework. Methods: In this mixed methods study, we recruited four diverse UK-based organisations to co-produce bespoke Sit Less at Work interventions with staff volunteers using the socioecological model as a framework via two workshops per organisation. Initiatives included communications from senior leaders, incorporating sitting less into policies, step competitions, and regular sitting breaks. Only three organisations (a small business, a charity, and a local authority) went on to implement the co-produced interventions between Sept 10, 2018, and May 5, 2019. These organisations all participated in a mixed-methods implementation and process evaluation of these interventions. Data collection included questionnaires, objective measures of workplace sitting time, focus groups, and interviews. Convenience samples of participants were recruited by email to measure sitting time before and after implementation and all participants were also invited to take part in focus groups. We analysed both the quantitative and qualitative data and identified key themes relating to contextual factors. All participants provided written informed consent. Ethical approval was obtained from the School of Health and Related Research Ethics Committee at the University of Sheffield (ref no 019368). Findings: 57 participants initially volunteered to provide intervention measures (small business n=5, charity n=11, and local authority n=41). 52 provided sitting times as baseline, 40 at 12 weeks (during the final week of the intervention), and 31 at 3 months post-intervention. 57 participants completed the questionnaire at baseline, 46 at 12 weeks, and 34 at 3 months post-intervention. 16 participants attended the focus groups (small business n=3, charity n=3, local authority n=10), and six were interviewed (n=1, n=2, and n=3, respectively). Process evaluation found none of the interventions was implemented as intended, with no consistent reduction in sitting: for the small business the mean proportion of time spent sitting at work was 82% (SD 11) at baseline, 77% (7) at 12 weeks, and 83% (7) 3 months post-intervention; for the charity it was 75% (9) at baseline, 77% (6) at 12 weeks, and 72% (15) at 3 months post-intervention; for the local authority it was 72% (14), 73% (14), and 68% (16), respectively. Contextual and cultural barriers to implementation included ingrained social norms that assume working involving sitting, the workplace being designed for sitting, workload pressures, lack of management buy-in, and perceptions of where the responsibility for behaviour change should come from. Interpretation: Development, implementation, and evaluation of initiatives designed to encourage workers to sit less require careful consideration of important contextual factors that influence the modern workplace. To ensure effective implementation of future initiatives, deeper organisational-level change requiring buy-in from all levels of management and staff might be needed to shift organisational culture and associated social norms. The operational framework can be used by researchers and practitioners to ensure consideration is given to these contextual factors and to support the development and delivery of more effective interventions. Funding: UK National Institute for Health Research (NIHR) Doctoral Research Fellowship Programme.